2019
DOI: 10.1177/2331216519872378
|View full text |Cite
|
Sign up to set email alerts
|

FreeHear: A New Sound-Field Speech-in-Babble Hearing Assessment Tool

Abstract: Pure-tone threshold audiometry is currently the standard test of hearing. However, in everyday life, we are more concerned with listening to speech of moderate loudness and, specifically, listening to a particular talker against a background of other talkers. FreeHear delivers strings of three spoken digits (0–9, not 7) against a background babble via three loudspeakers placed in front and to either side of a listener. FreeHear is designed as a rapid, quantitative initial assessment of hearing using an adaptiv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
15
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 19 publications
(15 citation statements)
references
References 35 publications
0
15
0
Order By: Relevance
“…42,43 Other studies have found that BILDs increase with increasing age. 44 Some studies report that spatial release of masking is adult-like at a young age (e.g., 4-6 years) [45][46][47] while others show a developmental trajectory. 26,48,49 Practically, age-specific normative criteria should be available for the diotic and antiphasic DIN, to relate the results of children tested to that of their peers.…”
mentioning
confidence: 99%
“…42,43 Other studies have found that BILDs increase with increasing age. 44 Some studies report that spatial release of masking is adult-like at a young age (e.g., 4-6 years) [45][46][47] while others show a developmental trajectory. 26,48,49 Practically, age-specific normative criteria should be available for the diotic and antiphasic DIN, to relate the results of children tested to that of their peers.…”
mentioning
confidence: 99%
“…It has been found to be usable with children aged four and above ( Neumann et al., 2012 ; Wagener et al., 2006 ). Another speech test that was designed for the use with children is ‘FreeHear,’ which is available in British English ( Moore et al., 2019 ). In this test, three spoken digits are presented against a background of babble noise.…”
mentioning
confidence: 99%
“…Recently, Moore and colleagues (2019) developed a DIN test that uses sound-field presentation of digits against a multi-talker babble masker (“FreeHear”). The masker is either co-located with the digits (0°), or presented 90° either side of the participant, enabling measurement of spatial ‘release from masking’, the benefit received from a spatial mis-match between target and masker.…”
Section: Discussionmentioning
confidence: 99%